Relationship between CPOD and limitation to brush teeth in schoolchildren from Sagrario Cuenca Ecuador - Pacurucu-Pinos, Elizabeth E. (2021)
Objectives: The objective of this study was to relate the CPOD index and limitation of brushing teeth in 12-year-old schoolchildren of the El Sagrario parish in 2016. Materials and Methods: The present study has a quantitative, descriptive, retrospective relational approach. The sample consisted of 155 observation files consisting of: registration number, age, sex, parish, CPOD index and limitation to brush teeth. Results: It was represented by tables and bar graphs; used the statistical analysis of Tau_b Kendall. Both sexes presented a very low level with respect to the DMFT index, in terms of impact and severity in brushing their teeth, the male sex presented a limitation with a lower percentage than the female sex. Conclusion: There was a very low correlation between the study variables.